2009
DOI: 10.1016/j.jacc.2008.12.073
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding, Blood Transfusion, and Increased Mortality After Percutaneous Coronary Intervention

Abstract: Advances in percutaneous coronary intervention (PCI) during the past decade have led to more widespread use of these procedures in older and sicker patients. Refinement of periprocedural antithrombotic therapy has played a particularly important role in reducing ischemic complications to very low levels in routine practice. Although the use of more powerful antiplatelet agents has been associated with increased risk of bleeding (especially among the elderly and patients with serious comorbidities), such compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
232
0
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(249 citation statements)
references
References 74 publications
5
232
0
12
Order By: Relevance
“…It should be noted that similar results were found in other studies 14, 23. Moreover, several studies14, 31, 32 found that major bleeding was associated with increased risk of death, and bleeding was dangerous not only because of the hemorrhage itself but also because it forced the discontinuation of necessary anticoagulation, which might induce higher rates of thrombotic events. Disturbingly, bleeding events might be underestimated in studies, and the impact of bleeding could be even larger in real life than reported in these studies, because these studies were not specifically designed to detect bleeding events; this could explain why the rate of bleeding events reported in the WOEST trial12 was much higher than those in other studies 6, 15, 19, 20, 22.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that similar results were found in other studies 14, 23. Moreover, several studies14, 31, 32 found that major bleeding was associated with increased risk of death, and bleeding was dangerous not only because of the hemorrhage itself but also because it forced the discontinuation of necessary anticoagulation, which might induce higher rates of thrombotic events. Disturbingly, bleeding events might be underestimated in studies, and the impact of bleeding could be even larger in real life than reported in these studies, because these studies were not specifically designed to detect bleeding events; this could explain why the rate of bleeding events reported in the WOEST trial12 was much higher than those in other studies 6, 15, 19, 20, 22.…”
Section: Discussionmentioning
confidence: 99%
“…Criteria for including legal cases were as follows: (1) cases that involved patients who underwent diagnostic catheterization and/or PCI for any indication (primary PCI, rescue PCI, and elective PCI) and (2) cases that reported retroperitoneal hemorrhage after the respective procedure was performed. Each case was thoroughly reviewed and information about the date the case was decided, the plaintiff, the defendant, the claim, and trial outcome were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…Risks associated with TFA PCI include access site bleeding and other major vascular complications, with retroperitoneal hematoma being one of them, leading to higher risk of subsequent morbidity, mortality, and increase in length of stay and cost. [2] Retroperitoneal hemorrhage is an uncommon but potentially fatal complication of TFA PCI occurring in approximately 0.5-0.74% of transfemoral procedures. [3][4] Female gender, low body surface area, chronic renal failure, use of glycoprotein IIb/IIIa inhibitors, presentation with acute myocardial infarction (MI), and high placement of the sheath (above the inferior epigastric artery) have been reported as the most significant risk factors for retroperitoneal hemorrhage in various studies.…”
Section: Introductionmentioning
confidence: 99%
“…However one problem that continues to haunt the cardiologists is the considerable incidence of bleeding complications following PCI. 1 We are now well aware that bleeding complications following PCI not only increased mortality and morbidity pre-discharge but also in the long term. The reasons for this could be several including the physical effects of blood loss, bleeding into critically important areas like brain, the need to discontinue antiplatelet therapy and the need for blood transfusions with its attendant adverse effects like reduced ability of blood to transfer oxygen, TRIM (transfusion related immune modulation) and so on.…”
mentioning
confidence: 99%
“…The reasons for this could be several including the physical effects of blood loss, bleeding into critically important areas like brain, the need to discontinue antiplatelet therapy and the need for blood transfusions with its attendant adverse effects like reduced ability of blood to transfer oxygen, TRIM (transfusion related immune modulation) and so on. 1 Therefore any new modalities adopted to reduce bleeding complications are welcome like radial route for PCI. The recently published RIVAL study randomized patients of acute coronary syndromes to radial or femoral access during PCI.…”
mentioning
confidence: 99%